Development of Project-Based Islamic Education Teaching Materials to Foster Values of Trustworthiness and Collaboration in Grade IV Students at Cidadap State Elementary School - Adudin Alijaya, Adudin; Sumpena, Rd. Panji; Muztaba, Asep; Saepudin, Saepudin; AS, Haerudin; Rosi, Dinyati (STAI Miftahul Ula Nganjuk, 2025)
This study aims to develop Islamic Religious Education (PAI) teaching materials based on Project-Based Learning (PBL) to foster the values of trustworthiness and collaboration among fourth-grade students at Cidadap Elementary School, West Pagaden District, Subang Regency. Employing a Research and Development (R&D) approach, the study adopts the ADDIE development model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The analysis stage was conducted to identify students' learning needs and existing conditions. The design and development phases produced project-based thematic modules, which were validated by experts in content, media, and instructional design. The implementation results demonstrate that the developed materials effectively enhance students’ active participation in learning and promote a sense of responsibility (trustworthiness) and teamwork (collaboration). Evaluation was conducted using observations, questionnaires, and pre- and post-tests, all of which indicated a significant improvement in students’ comprehension and character development. The study recommends the integration of PjBL-based PAI teaching materials as an innovative approach to support contextual and applicable character education in elementary schools.